Epidemiological Study of Prostate Neoplasms in Maragheh City During 2014-2019: Northwestern of Iran - Ahmad Vahednasiri (Shahrekord University of Medical Sciences, 2021)
Background and aims: Prostate neoplasms have various geographical distribution in the world as well as in Iran. This study aimed to investigate the epidemiology of prostate neoplasms in Maragheh due to the lack of literature on the subject in this city.   Methods: This study is a descriptive-analytical, cross-sectional study in which the epidemiological status of prostate neoplasms was investigated in Maragheh during 2014-2019. All available records in the form of a census were included in the study. A checklist made by the researcher was used as a special tool for collecting data from prostate neoplasms medical records. The collected data were analyzed by statistical tests of chi-square, unpaired t test, Kruskal-Wallis test, and Cohen's kappa coefficient using SPSS 25 software.   Results: By way of explanation, 107 medical records on prostate neoplasms were recorded between 2014 and 2019. The mean and median ages were 71.33 ± 9.37 and 70 years. The highest frequency was observed in the 60-70 age group with a frequency of 41.1% (44 cases). All patients had been undergoing clinical examination (first) and pathological examination (after prostatectomy). For 12.1% of individuals, benign prostatic hyperplasia (BPH) had been diagnosed in the clinical diagnosis, and cancer and prostatitis had been diagnosed in the pathological test. Cohen's kappa coefficient was obtained 20.4%, which was statistically significant (p ≤0001). The results showed a significant relationship between the number of prostate neoplasms and age groups (p ≤0001).   Conclusion: Taking the results of this study into account, it is recommended that more attention be paid to other laboratory and radiological tests such as the PSA test, ultrasound, etc. In addition to clinical examination, it is also suggested that screening programs be particularly developed for the age group ≥50 using a specific prostate antigen against this cancer.